Review of clinical outcomes-based anchors of minimum clinically important differences in hip and knee registry-based reports and publications. - Romero, L; Nieuwenhuijse, M; Carr, A; Sedrakyan, A (2014)
Patient-reported outcome measures are tools that allow clinicians and researchers to gauge patients' level of satisfaction and quality of life after a medical intervention. The use of patient-reported outcome measures and the clinically relevant score differentials over time as they relate to outcomes (minimum clinically important differences) has been proposed as a way to understand success and failure rates in orthopaedics. We conducted a systematic appraisal of literature in peer-reviewed journals and registry reports to measure the use that registries and other large data repositories make of minimum clinically important differences and to understand methodological approaches for such uses. Of the nineteen registry reports and 1052 articles examined, we found that only one report and two studies mentioned the use of patient-reported outcome measures and minimum clinically important differences in the context of revision rates of total knee arthroplasty and total hip arthroplasty. We conclude that although the infrastructure and efforts to routinely collect patient-reported outcome measures at registry levels do exist, there is limited use of minimum clinically important differences to understand and potentially predict clinical outcomes. We suggest advancing the global infrastructure such as the International Consortium of Orthopaedic Registries to address how research related to patient-reported outcome measures can help individual registries collaborate in the development of tools and allow aggregation of data.